A Critical Analysis of the Visual Notation for Team Design Patterns - Fleiner, Christian; Zvekan, Goran; Hatas, Tomas (ACM International Conference Proceeding Series, 2023)
We review and analyze the original notation for team design patterns and its visual dialects that aim to foster discussions about human-agent collaboration. The analysis addresses the concrete syntax, the semiotic clarity, the semantic transparency, and the diagrammatic complexity. While the notation is powerful, the results indicate that the notation has still shortcomings that might hinder its worldwide adoption.
CRIS-Team Scopus Importer:2023-12-29
Keywords: diagrams; human-agent collaboration; human-agent teaming; joint activity; modeling; team design patterns